The successful experience of IGCP636 project "unifying international research forces to unlock and strengthen geothermal exploitation of the Americas and Europe" (2019)
Geothermal fluids are extracted through deep wells drilled in a geological reservoir, which can be represented by highly heterogeneous volcanic complex, sedimentary basins or deep basement rocks. The main objective of this project was to propose suitable methodologies and techniques for the characterization and modeling of fractured geothermal reservoirs, to ensure their sustainable exploitation and, therefore, ensure acceptation of this kind of energy by local communities. This goal was achieved with experiences from the volcanic complex of the Nevado del Ruiz (Colombia), the St. Lawrence Lowlands sedimentary basin (Québec, Canada), the Carboniferous limestone reservoir in the area of Mons (Belgium), the Soultz-Sous-Forêts power plant and the Ploemeur fractured rock hydrogeological experimental site (France), and various areas of interest for geothermal exploration in Chile. The work conducted provided new insights into the construction of conceptual and numerical models for geothermal reservoirs and allowed the creation of a solid research network between Europe and Americas, fostering participation in geosciences of young researchers, students, and women. © 2019 International Union of Geological Sciences. All rights reserved.